2011
DOI: 10.1016/j.yebeh.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Transection of CA3 does not affect memory performance in rats

Abstract: Longitudinal hippocampal pathways are needed for seizure synchronization, and there is evidence that their transection may abolish seizures. However, the effect of such transection on memory is unknown. In this study, we investigated the effect of transverse CA3 transections on memory function in Sprague-Dawley rats. Using a stereotactic knife, a single CA3 transection was made unilaterally (n=5) or bilaterally (n=5). Sham surgery was done in another group (n=4). Morris water maze (MWM) and Novel object recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The functional significance of dendritic remodeling in terms of absolute impact on hippocampus processing has remained elusive. Supporting our data showing no significant MWM score differences despite of reduced dendritic arborization in this pyramidal cell layer, recently, Koubeissi et al (2011) have demonstrated that bilateral cuts of the CA3 dorsal hippocampus layer did not affect MWM scores in rats.…”
Section: Discussionsupporting
confidence: 90%
“…The functional significance of dendritic remodeling in terms of absolute impact on hippocampus processing has remained elusive. Supporting our data showing no significant MWM score differences despite of reduced dendritic arborization in this pyramidal cell layer, recently, Koubeissi et al (2011) have demonstrated that bilateral cuts of the CA3 dorsal hippocampus layer did not affect MWM scores in rats.…”
Section: Discussionsupporting
confidence: 90%
“…Intermittent incisions perpendicular to the longitudinal axis of the hippocampal formation from its ventricular surface at 4-to 5-mm intervals without ablation of fimbria are expected to inhibit abnormal longitudinal synchronization and thus abolish epileptic activity, while preserving the intrahippocampal neural circuitry and, ultimately, memory function. 6,7 The seizure outcome of MHT at 1 year after surgery was equivalent to that of temporal lobectomy, and the memory indices were preserved at the preoperative level. 5 Although other groups subsequently reported similar results, 8,9 the long-term outcomes after MHT still remain to be clarified, because of the small patient numbers and the limited periods of follow-up in those studies.…”
Section: Discussionmentioning
confidence: 91%
“…It is a hippocampal counterpart to multiple subpial transection (MST), which is applied to the neocortices. Intermittent incisions perpendicular to the longitudinal axis of the hippocampal formation from its ventricular surface at 4‐ to 5‐mm intervals without ablation of fimbria are expected to inhibit abnormal longitudinal synchronization and thus abolish epileptic activity, while preserving the intrahippocampal neural circuitry and, ultimately, memory function …”
mentioning
confidence: 99%
“…22,23 Although the concept of HT was a proposed hypothesis, not an accepted doctrine, recent studies have described detailed electrophysiological observations in humans 25 and memory preservation in rat models 12 that support the theory and efficacy of HT. However, in the previous literature, the important processes of the surgery and the depth and extent of transection were ambiguous.…”
Section: Discussionmentioning
confidence: 99%